Afterword: Dark Anthropology in Papua New Guinea? - Jorgensen, Dan (The Australian journal of anthropology, 2019)
Ranging from colonial modernism to postcolonial disappointment, the papers in this collection explore the possibilities of Dark Anthropology and an Anthropology of the Good in Papua New Guinea. With these two prospects in mind, I consider what these papers tell us about the situations of rural people on the peripheries of large resource projects and those in ‘Last Places’ bypassed by development and the State. In all of these cases, difficult predicaments entail hardship or suffering, but are also met with responses seeking to realise varying versions of the good. This, in turn, prompts further questions about which and whose good are at issue amid a plurality of values. I conclude by suggesting that the ensemble of papers offers a retrospective on local versions of modernity as possibility contends with experience.